2015
DOI: 10.4115/jla.2014.6.8
|View full text |Cite
|
Sign up to set email alerts
|

Measure, category and projective wellorders

Abstract: We investigate the sample path properties of Martin-Löf random Brownian motion. We show (1) that many classical results which are known to hold almost surely hold for every Martin-Löf random Brownian path, (2) that the effective dimension of zeroes of a Martin-Löf random Brownian path must be at least 1/2, and conversely that every real with effective dimension greater than 1/2 must be a zero of some Martin-Löf random Brownian path, and (3) we will demonstrate a new proof that the solution to the Dirichlet pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…3 well-orders of the reals There has been significant interest in the study of possible constellations among the classical cardinal characteristics of the continuum in the presence of a projective, in fact ∆ 1 3 -definable, well-order of the reals (see [FF10,FFZ11,FFK14]). Answering a question of [FFK14], we show that each of the constellations described in the previous section is consistent with the existence of such a projective well-order. Since the proofs for the different constellations are very similar, we will only outline the proof of the following theorem.…”
Section: mentioning
confidence: 99%
See 2 more Smart Citations
“…3 well-orders of the reals There has been significant interest in the study of possible constellations among the classical cardinal characteristics of the continuum in the presence of a projective, in fact ∆ 1 3 -definable, well-order of the reals (see [FF10,FFZ11,FFK14]). Answering a question of [FFK14], we show that each of the constellations described in the previous section is consistent with the existence of such a projective well-order. Since the proofs for the different constellations are very similar, we will only outline the proof of the following theorem.…”
Section: mentioning
confidence: 99%
“…In [FF10] it is shown for example that various constellations involving a, b and s are consistent with the existence of a ∆ 1 3 well-order, while in [FFK14] it is shown that every admissible assignment of ℵ 1 and ℵ 2 to the characteristics in Cichoń's diagram is consistent with the existence of such a projective well-order. There is one main distinction between the various known methods for generically adjoining projective wellorders: methods relying on countable support S-proper iterations like in [FF10,FFK14], and methods using finite support iterations of ccc posets, e.g. [FFZ11,FFT12,FFZ13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results for classes Σ 1 2 , Σ 1 2 are obtained by an elementary argument. On these and other theorems on uniformization and related questions see references above, as well as [37,34,10,4,7,6] with respect to modern studies, and also in the introductory section of our paper [16].…”
Section: Introductionmentioning
confidence: 92%
“…By definition, the multitree R ′ = ϕ(k, m ′ ) is an m ′ -collage over S ↑ , and then m-collage, too, by Lemma 9.3(i), where m = m ′ + 1. 6 To prove the openness let T ∈ D. Then T ↑ ∈ D ↑ , S ∈ S, and S ↑ T ↑ . We cannot assert directly that S T. However the multitree S ′ = S↑ (|T| ∪ |S|) also belongs to S by Definition 9.1(III).…”
Section: Validation Of 123(b)mentioning
confidence: 99%